2015
DOI: 10.1007/s13402-015-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SOX11 promoter methylation is associated with poor prognosis in gastric cancer

Abstract: Our results indicate that aberrant SOX11 gene promoter methylation may underlie its down-regulation in GC. SOX11 gene promoter hyper-methylation may serve as a biomarker to predict the clinical outcome of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Using IHC, reverse transcription–polymerase chain reaction (RT–PCR) or Western blot, SOX11 has been found to be down‐regulated in several malignant epithelial tumours, such as prostate, gastric and nasopharyngeal carcinomas via hypermethylation, and in these epithelial tumours SOX11 functions as a tumour suppressor gene that is associated with tumour growth and invasion . In this study, SOX11 expression was completely absent in all the aforementioned carcinomas, as well as most other adenocarcinomas and carcinomas that originated from the squamous, urinary and thymic epithelia using IHC (Table ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Using IHC, reverse transcription–polymerase chain reaction (RT–PCR) or Western blot, SOX11 has been found to be down‐regulated in several malignant epithelial tumours, such as prostate, gastric and nasopharyngeal carcinomas via hypermethylation, and in these epithelial tumours SOX11 functions as a tumour suppressor gene that is associated with tumour growth and invasion . In this study, SOX11 expression was completely absent in all the aforementioned carcinomas, as well as most other adenocarcinomas and carcinomas that originated from the squamous, urinary and thymic epithelia using IHC (Table ).…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, there are a few reports demonstrating SOX11 expression in mRNA and proteins of some malignant epithelial tumours. [14][15][16][17][18] However, the expression and significance of SOX11 using immunohistochemistry (IHC) analysis in different tumour types has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…), gastric cancer (Xu et al . ) and nasopharyngeal carcinoma (Zhang et al . ), but not in prostate cancer cells or tissues.…”
mentioning
confidence: 99%
“…SOX11 plays an important role in the development of the neural system (Hyodo-Miura et al 2002;Wang et al 2013). Several functional and clinicopathological studies demonstrated that SOX11 acts as a tumour suppressor in solid cancers (Hide et al 2009;Sernbo et al 2011;Zhang et al 2013;Xu et al 2015). Yao et al (2015) reported downregulation of SOX11 in prostate adenocarcinoma tissue compared to benign prostatic hyperplasia (BPH).…”
mentioning
confidence: 99%
See 1 more Smart Citation